Open-end debt investment funds and bank deposits in Poland 1995-2015. A comparison of the a posteriori probability (chance) of failure to achieve the level of aspiration - Dittmann, Iwona (Dłużne otwarte fundusze inwestycyjne oraz depozyty bankowe w Polsce w latach 1995-2015. Porównanie a posteriori prawdopodobieństwa (szans) nieosiągnięcia poziomu aspiracji, 2016)
The aim of the study was to compare, a posteriori, the probabilities (chances) of failure to achieve the level of aspiration (expressed in expected rates of return) on open-end debt investment funds (debt OEF), as well as the rates of return on bank deposits in Poland in light of different investment horizons. The data covered the periods of operation of each individual fund. The values for the probability of not achieving the level of aspiration (PNAL) have been calculated on the basis of empirical probability distributions of the rates of return on funds and bank deposits, obtained through the use of a rolling window of observation. Studies have shown the existence of a lower limit for the level of aspiration, the achievement of which is required in order for investment in a fund to be chosen over investment in a bank deposit. Based on research on the investment horizons which had, in the past, guaranteed the achievement of a given rate of return on a fund, both good and bad funds were identified. The results were largely influenced by the very high interest rate on bank deposits in Poland in the period 1995 – 2001 (in the case of the oldest funds) and by the boom on the Treasury bond market in 2011 – 2012 (for the youngest funds)
Ekonometria = Econometrics, 2016, Nr 2 (52), s. 77-97
Keywords: personal finance; investment fund; bank deposit; comparative analysis; finanse osobiste; fundusze inwestycyjne; depozyty bankowe; analiza porównawcza